2012
DOI: 10.1111/j.1524-4725.2012.02526.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hyfrecators and Their In Vitro Interference with Implantable Cardiac Devices

Abstract: Hyfrecators are safe to use in patients with defibrillators and can be used in pacemaker patients within 2 inches of the device perimeter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…25 A recent study of hyfrecators (both monoterminal and biterminal, electrodesiccation and electrofulguration methods) found significant interference with pacemakers within 3 cm of the device and no significant interference with ICDs. 26 These data support the safe use of electrosurgery in the dermatology outpatient setting. It is still prudent to consider methods such as bipolar handpieces and temporary device deactivation to mitigate risk in these patients.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 60%
“…25 A recent study of hyfrecators (both monoterminal and biterminal, electrodesiccation and electrofulguration methods) found significant interference with pacemakers within 3 cm of the device and no significant interference with ICDs. 26 These data support the safe use of electrosurgery in the dermatology outpatient setting. It is still prudent to consider methods such as bipolar handpieces and temporary device deactivation to mitigate risk in these patients.…”
Section: Safety In An Office-based Setting Key Pointsmentioning
confidence: 60%
“…The authors investigated safety margins and reported that for pacemakers, atrial inhibition was observed at 3 cm on maximum hyfrecator settings and 1 cm at normal use settings. 29 A recent in vivo retrospective study did not report adverse perioperative effects in patients with implantable cardiac devices. 30 …”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…However, a 2012 study by Weyer et al found that electrodessication with a Hyfrecator on maximal settings can be used safely beyond a 3-cm radius around the implanted device. The hyfrecator can also safely be used beyond a 1-cm radius with standard settings (Weyer et al, 2012). To improve the safety of the hyfrecator, the operator can use short bursts of electricity to decrease the possibility of prolonged periods of inhibition (approximately 1 second bursts; Matzke et al, 2006).…”
Section: Preoperative Assessment and Surgical Considerationsmentioning
confidence: 99%
“…To improve the safety of the hyfrecator, the operator can use short bursts of electricity to decrease the possibility of prolonged periods of inhibition (approximately 1 second bursts; Matzke et al, 2006). In patients who are oxygen-dependent, oxygen flow should be temporarily discontinued while using electrical means of hemostasis because the spark could ignite a fire (Weyer et al, 2012).…”
Section: Implantable Devicesmentioning
confidence: 99%